On the Definition of a Method for Specifying Accessibility Requirements: Early Insights from a Focus Group with Practitioners’ - Vinadé, Renata; Goelzer, Natalya; Marczak, Sabrina (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2025: Anais do XXXIX Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2025.11561, 2025)
Accessibility remains a significant challenge in software development, often due to the lack of structured and actionable guidance for specifying requirements that address diverse user needs. This paper introduces Path4All, a lightweight and user-centered method that integrates Personas, User Stories (US), Behavior-Driven Development (BDD), and WCAG guidelines to support the clear and consistent specification of accessibility requirements. To gather early insights into the method’s applicability, we conducted a focus group with experienced software professionals who applied Path4All in a practical, scenario-based activity. The findings suggest that Path4All fosters empathy, improves requirement clarity, and promotes the production of actionable and inclusive specifications. Participants highlighted the method’s potential benefits, while also identifying challenges related to WCAG complexity, organizational culture, and the need for clearer role definitions. These initial results point to Path4All’s potential to support inclusive design practices from the early stages of development.